Prevalence and clinical correlates of chronic kidney disease among hospital admissions in KwaZulu-Natal: A cross-sectional retrospective laboratory data analysis. - Masuku, Mpilonhle; Bhengu, Khethiwe Nomcebo (Student's Journal of Health Research Africa, 2026)
Background: Chronic kidney disease (CKD) is a non-communicable disease that causes a significant global health burden yet is commonly underdiagnosed among hospitalised patients, particularly in acute care facilities. Timely diagnosis is crucial in preventing disease progression and poor prognosis due to complications. Aim: This study estimated the prevalence of CKD among hospital admissions and assessed its relationship with clinical diagnoses and ward distribution, laboratory parameters in a referral hospital in South Africa. Methods: A retrospective observational analysis was conducted using laboratory records from RK Khan Hospital in KwaZulu-Natal. Patients with documented serum creatinine levels and estimated glomerular filtration rates (eGFRs) were included. CKD was defined as eGFR < 60 mL/min/1.73 m², calculated using either the MDRD or CKD-EPI equations. Demographic data, ward allocation, clinical diagnoses, and laboratory parameters were analysed descriptively. Results: Analysis of the complete dataset (n=56) revealed that 39 patients (69.6%) met the criteria for CKD (eGFR < 60 mL/min/1.73m²). The highest prevalence was observed in the 45–59 age group (40%). The study population had a mean age of 47.5 years (range, 19-64 years). Admissions were primarily to the Intensive Care Unit (57.1%), followed by the outpatient and emergency departments. Among CKD patients, the most common comorbid diagnoses were pneumonia and septicaemia. Severe renal impairment (eGFR < 30 mL/min/1.73m²) was present in 28.6% of cases, and frequent electrolyte disturbances, including hyperkalaemia and metabolic acidosis, were observed. Conclusion: CKD is notably prevalent among hospitalized patients, particularly those admitted with infectious diseases or critical illnesses. These findings underscore the importance of systematic surveillance of renal function in acute care settings. Recommendations: The integration of standardized CKD screening protocols into routine hospital care may help mitigate disease progression and improve clinical outcomes.